Problematika Penggunaan Bahasa Indonesia dalam Komunikasi Akademik Mahasiswa Jurusan Pendidikan Ekonomi Universitas Negeri Gorontalo di Era Digital - Indri Rahmawati Dunggio; Susan Tilola; Aura Aprilianti Katili; Rahmiyati Hakim; Indra Laiya; Zahra Idris Basalamah; Nuryana Sartin Kai; Noraliza Sudarman; Ismail Utina; Ade Saputra Nusi; Meilina Widya Dali (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
This study aims to describe the use of Indonesian in academic communication among students of the Economics Education Study Program at Gorontalo State University, identify emerging problems and their reasons, and examine their impact on message delivery and understanding of economic concepts. This study used a qualitative approach with descriptive methodology. Data were collected through semi-structured interviews, observations of classroom presentations and discussions, and documentation of digital academic communication in the form of WhatsApp conversations, Google Classroom interactions, and presentation transcripts. The study participants consisted of 10 students selected through purposive sampling in the second semester. The results indicate that the use of academic Indonesian is not optimal. Students still use colloquial language, slang, informal abbreviations, and foreign terms in both oral and digital academic communication. This situation is influenced by informal language habits, the influence of social media, low practice in academic communication, and limited exposure to scientific language. The impact is evident in the lack of clarity in conveying ideas and understanding of economic concepts. Therefore, consistent use of academic Indonesian is needed in the university environment.